Faktor-Faktor Yang Mempengaruhi Terjadinya Infeksi Luka Post Sectio Caesarea - Murniati; zulkarnaini; Zeva Juwita (STIKes Darussalam Lhokseumawe, 2020)
Post sectiocaesarea wounds are scars that leave scars and are caused by Caesarean section when women cannot give birth normally. The mortality rate directly related to Surgical Site Infection (SSI) ranges from 3% to 75% in hospitals worldwide. The incidence of SSI in hospitals worldwide has increased from 21.2 cases per 100 surgical procedures to 23.6 cases per 100 surgical procedures. The purpose of the study was to determine the factors that influence the occurrence of post Sectio Caesarea wound infection at the Cut Meutia General Hospital, North Aceh Regency. This research is analytical research with a cross sectional study. The population were all post Sectio Caesarea patients at the Cut Meutia General Hospital, North Aceh Regency, amounting to 64 people. The sampling technique was accidental sampling totaling 43 people. Data were collected by distributing observation form. The results showed that the age of the patients post Sectio Caesarea were mostly in the no-risk category (76.7%), the preoperative Fasting Blood Glucose Levelwere mostly in the normal category (97.7%), the preoperative albumin levels were mostly in the normal category (88.4%), and the majority of post-sectiocaesarea patients did not experience post-sectiocaesarea wound infections (79.1%). The results of the Chi Square test showed that the variables that influenced the incidence of post Sectio Caesarea wound infection at Cut Meutia General Hospital, North Aceh Regency were age (p = 0.002) and Albumin Level (p = 0.000).